Managerial Competence and Entrepreneurial Mindset on MSME Growth: The Mediating Role of Education and Training - Hajrawati Hajrawati; Muazza Muazza; Kuswanto Kuswanto (Electronic Journal of Education, Social Economics and Technology, 2026)
Village-level Micro, Small, and Medium Enterprises (MSMEs) in Indonesia face persistent qualitative growth stagnation despite increases in enterprise numbers, driven largely by underdeveloped internal human capital and structurally misaligned training programs. Understanding which internal capabilities most powerfully drive MSME growth, is critical for designing evidence-based development interventions. This study investigates the direct effects of managerial competence and entrepreneurial mindset on MSME growth, their effects on education and training participation, and the mediating role of education and training between these capability constructs and MSME growth. A quantitative explanatory approach was employed using a saturated sampling technique that included all 61 active MSME actors in Tangkit Baru Village, Muaro Jambi Regency, Jambi Province. Data were collected through structured Likert-scale questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. Entrepreneurial mindset emerged as the dominant and singular direct determinant of MSME growth, with a large effect size, while managerial competence did not directly and significantly affect growth. Both capability constructs significantly and positively influenced education and training participation, with managerial competence producing a stronger effect. Education and training, however, did not function as an effective mediator in either pathway, reflecting a structural relevance gap between available program content and actors' strategic growth needs. MSME development programs must prioritize entrepreneurial mindset cultivation through experiential and action-learning approaches, while training content must be fundamentally redesigned toward market strategy, financial literacy, and digital capability development to activate its mediating potential